(untitled) (Studia Prawnicze / The Legal Studies, 2010)
Uregulowania prawne dotyczące sposobu przenoszenia prawa własności nieruchomości nie zawsze pozwalają na zawarcie umowy sprzedaży przyszłej nieruchomości ze skutkiem rozporządzającym. Tak jest zarówno w polskim, jaki i niemieckim systemie prawnym. Także rozwiązania prawne przyjęte w angielskim systemie prawnym nie pozwalają na zawarcie umowy sprzedaży przyszłej nieruchomości ze skutkiem rozporządzającym. Natomiast we Francji, ustawodawca zdecydował się na przyjęcie konstruktywnego modelu umowy sprzedaży rzeczy przyszłej w postaci budowanej nieruchomości budynkowej, ze skutkiem zobowiązująco-rozporządzającym. Wreszcie modelowe rozwiązania umowy sprzedaży przyjęte w Draft Common Frame of Reference – choć wykluczają ich zastosowanie do przenoszenia praw do nieruchomości – wyraźnie wskazują na współczesną tendencję do szerokiego zastosowania konstrukcji umowy sprzedaży rzeczy przyszłej. W ujęciu modelowym, obejmuje ona swoim zakresem także zobowiązanie sprzedającego do wytworzenia rzeczy, a nie li tylko do przeniesienia własności tej rzeczy. Taka formuła umowy sprzedaży rzeczy przyszłej odpowiada jej podstawowym założeniom i pozwala odróżnić ją od innego rodzaju umów, jak umowa o dzieło - wytworzone z materiałów zleceniobiorcy - lub umowa dostawy In this article the author presents the construction and functions of a contract of sale of future goods, in particular pertaining to real property under construction. The sale of future goods contract guarantees the buyer that he will obtain the property right of the sold good automatically upon its existence (or sometimes at a later stage), the seller, that he will sell this good to the buyer. Consequently, the buyer may gain from the fact that the seller will not sell such goods to a third party and the seller may gain the price paid upon the signature of the contract, which will enable him to finance the construction of the future good. Such benefits of the sale of future goods contract can also be used in order to sell real property that is under construction. The guarantee and financing function of the sale of future goods contract is especially important in real property development projects. The sale of future goods contract has been evolving since ancient times. Presently, this type of contract has been experiencing a dynamic evolution, especially in respect to future real property. Such an evolution is though subject to legal regulations pertaining to the transfer of ownership rights of real estates that are in force in different national legal systems. Polish regulations incorporated in the Civil code enable parties to conclude sale of future goods contracts. Upon the signature of such a contract, the buyer obtains the right to acquire the ownership right of the future good. The ownership right is transferred onto him at the time when the buyer obtains the possession the now existing future good. Regulations pertaining to sale of real property differ substantially in most European countries. In some, such as Poland and Germany, real property may not be sold under the condition that it will be erected by the seller, or a third party in the future. Only existing real property may be sold. Such regulations are justified by the need to ensure the certainty of real property sales. In other countries, such as France, future buildings or apartments may be sold under a contract La Vente l’Etat Futur d’Achevement (hereinafter called VEFA). Under such a contract the buyer acquires all the existing parts of the sold real estate, while the remaining part – which is to be constructed – is acquired by the buyer automatically during the process of the construction. The seller receives his remuneration upon the completion of consecutive stages of the construction process. Also it is important to mention the construction of the sale of future goods contract as regulated in the Draft Common Frame of Reference. There, apart from the obligation of the seller to transform onto the buyer the real property rights of the sold goods, the seller is obliged to make all other necessary actions in order to enable such a transfer of rights. If the Draft Common Frame of Reference would be referred to the sale of future real property under construction, such an obligation would include the obligation to construct the real property. The analysis in this article indicates that the sale of real property under construction has been regulated in some countries and that such constructions as VEFA have had a positive impact on these legal systems. Such regulations stimulate the real property development sector and ensure better protection of consumers buying future real property. Also, as it has been shown, that the European model rules of the Draft Common Frame of Reference clearly underline the importance of the sale of future goods functions. These – namely the guarantee and financing functions – may also be used in the construction of a sale of future real property contract.